EDUCATIONAL COSTING PLAN AS A STRATEGY FOR IMPROVING THE QUALITY OF EDUCATIONAL SERVICES - Rifa'i, Moh; Ainul Yaqin; Arif Maulana (Lembaga Penerbitan, Penelitian, dan Pengabdian kepada Masyarakat (LP3M) of Institut Badri Mashduqi Probolinggo Jawa timur Indonesia, 2023)
The Educational Costing Plan is a crucial financial planning for education that plays a significant role in realizing the quality of educational services in educational institutions. This is important to consider because the decision on cost estimation for all components of educational management in an educational institution will be well-thought-out, directed, and targeted to provide implemented services that continually improve in a cyclical manner. This research aims to find steps in planning cost estimation for all components of educational management, thereby serving as a strategy to enhance the quality of education services offered to the community in a specific manner. The research adopts a Systematic Literature Review (SLR) approach by using published research results from books, SINTA-indexed journals, or Scopus as the focus or references to be reviewed. The research findings indicate that cost planning can be a crucial strategy in improving the quality of educational services when implemented through steps such as using ESD as a reference for developing an Educational Financing Plan, formulating priority programs in education financing, analysing resources in school education financing, detailed recording of income and expenditure in RKAS, and planning the strengthening of work control systems and the use of educational cost.